ENHANCING TRANSLATION ACCURACY THROUGH COLLOCATIONAL AWARENESS: A LINGUISTIC AND COGNITIVE PERSPECTIVE (KONFERENSIYA, 2025)
Good translation involves more than just replacing words between languages. Itrequires an understanding of collocational patterns, which are common combinationsof words that have established meanings. This article looks at how being aware ofcollocations affects translation accuracy. Using ideas from phraseological theory,corpus linguistics, and psycholinguistic models, the research explores how learnershandle collocations during translation tasks. A mixed-methods approach was used,which included translation tests, surveys, and a detailed analysis of errors. The resultsindicate that learners who are more aware of collocations produce translations thatare much more natural, accurate, and idiomatic. The cognitive findings suggest thatcollocations ease the mental workload by acting as stored multiword units. This studysupports the need to include collocational training in translation education